Replication stress links structural and numerical cancer chromosomal instability - Burrell, Rebecca A. (Nature, 2013)
Cancer chromosomal instability (CIN) results in an elevated rate of change of chromosome number and structure and generates intratumour heterogeneity(1,2). CIN is observed in the majority of solid tumours and is associated with both poor prognosis and drug resistance(3,4). Therefore, understanding a mechanistic basis for CIN is paramount. Here we find evidence for impaired replication fork progression and elevated DNA replication stress in CIN+ colorectal cancer (CRC) cells relative to CIN− CRC cells, with structural chromosome abnormalities precipitating chromosome missegregation in mitosis. We identify three novel CIN-suppressor genes (PIGN (MCD4), RKHD2 (MEX3C) and ZNF516 (KIAA0222)) encoded on chromosome 18q, which is subject to frequent copy number loss in CIN+ CRC. 18q loss was temporally associated with aneuploidy onset at the adenoma-carcinoma transition. CIN-suppressor gene silencing leads to DNA replication stress, structural chromosome abnormalities and chromosome missegregation. Supplementing cells with nucleosides, to alleviate replication-associated damage(5), reduces the frequency of chromosome segregation errors following CIN-suppressor gene silencing and attenuates segregation errors and DNA damage in CIN+ cells. These data implicate a central role for replication stress in the generation of structural and numerical CIN, which may inform new therapeutic approaches to limit intratumour heterogeneity.